Seasonal hazards and health risks in lower-income countries: field testing a multi-disciplinary approach - Tran Pham; Hunter Paul R; Lake Iain; Few Roger; Thien Vu (BMC, 2009)
Abstract Understanding how risks to human health change as a result of seasonal variations in environmental conditions is likely to become of increasing importance in the context of climatic change, especially in lower-income countries. A multi-disciplinary approach can be a useful tool for improving understanding, particularly in situations where existing data resources are limited but the environmental health implications of seasonal hazards may be high. This short article describes a multi-disciplinary approach combining analysis of changes in levels of environmental contamination, seasonal variations in disease incidence and a social scientific analysis of health behaviour. The methodology was field-tested in a peri-urban environment in the Mekong Delta, Vietnam, where poor households face alternate seasonal extremes in the local environment as the water level in the Delta changes from flood to dry season. Low-income households in the research sites rely on river water for domestic uses, including provision of drinking water, and it is commonly perceived that the seasonal changes alter risk from diarrhoeal diseases and other diseases associated with contamination of water. The discussion focuses on the implementation of the methodology in the field, and draws lessons from the research process that can help in refining and developing the approach for application in other locations where seasonal dynamics of disease risk may have important consequences for public health.